Réponses

2014-05-10T13:35:16+02:00

B=(-1,4)+(+3,5)+(-6,7)-(+1,7)-(-4)

B= -1,4 + 3,5 - 6,7 - 1,7 + 4

B= -1,4 - 6,7 - 1,7 + 3,5 + 4

B= -8,1 - 1,7 + 3,5 + 4

B= -9,8 + 7,5

B= -2,3



 C= -5+2,7 +3,8-5,2-2,7+9,1-4,3

C= -5 - 5,2 - 2,7 - 4,3 + 2,7 + 3,8 + 9,1

C= -10,2 - 7 + 6,5 + 9,1

C= -17,2 + 15,6

C= -1,6

.. bon attend j'tenvoie un message privé
c'est ou les message priver ?
tout en haut à droite.
y'a rien
?!
2014-05-10T13:42:13+02:00
B= -1,4+ 3,5 - 6,7- 1,7 +4
= -1,4 - 6,7 - 1,7 +3,5 +4
= - 9,8 + 7,5
= - 2,3

C= -5+2,7 +3,8- 5,2 - 2,7+ 9,1- 4,3
= -5 - 2,7+ 2,7 - 5,2 -4,3 + 3,8 +9,1 
= -5 -5,2 -4,3 +3,8 +9,1
= -10,2 -4,3 + 12,9
= -14,5 + 12,9
= -1,6